Poorly Differentiated Thyroid Carcinomas - Kuru, B. (Ondokuz Mayis Universitesi Samsun 55139, 2012)
Poorly differentiated thyroid carcinomas (PDTC) show minimal differentiation and have a moderate prognosis that is between the prognosis of differentiated thyroid carcinomas and anaplastic carcinomas. PTDC generally have a large size usually associate with bone and pulmonary metastasis. PTDC have solid, trabecular and insular variants. The well known variant is insular carcinoma. They are potentially radioactive iodine (RAI) avid and therefore after complete surgery, RAI therapy is suggested for patients with PTDC. Proof for postoperative radiotherapy is poor. However, radiotherapy is offered for T3 tumors without remote metastasis and T4 tumors and for patients with regional lymph node metastasis. © 2012 OMU.
Kötü Diferansiye Tiroit Kanserleri
Keywords: Carcinomas; Insular Thyroid Carcinomas; Poorly Differentiated Thyroid Carcinomas; Thyroid Carcinomas; Treatment of Poorly Differentiated Thyroid